Pengaruh Pola Asuh Orang Tua Status Pemberian ASI Dan Status Gizi Terhadap Perkembangan Anak Usia Pra-Sekolah Di PAUD Puspita Kecamatan Cibadak Sukabumi Tahun 2021: The Effect of Parenting Patterns on Breastfeeding Status and Nutritional Status on the Development of Pre-School Age Children in PAUD Puspita, Cibadak District Sukabumi in 2021 - Nur Saadah, Fauziah (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: In World Health Organization data (2018), it was found that the prevalence of developmental deviations in children under 5 years of age in Indonesia reported by WHO in 2016 was 7,512.6 per 100,000 population (7,51%). About 5 to 10% of children are estimated to have developmental delays. Based on IDAI (2013), data on the incidence of general developmental delays are not known with certainty, but it is estimated that around 1-3% of children under the age of 5 years experience general developmental delays. Based on the Rikesdas in 2018, the number of early childhood development indexes in Indonesia reached 88,3% and in the province of West Java, it was 90%. Child development can be obtained by two factors, namely internal factors including genetics, including genetics, motivation, and training, while external factors include knowledge, attitudes, and education of parents, family, socioeconomic, environment, staff, and parenting styles.  Methods: This study used analytical survey research methods. In analytic survey research using a cross-sectional survey design. Sampling in this study was carried out by using a total sampan technique with a total sampling of 45 people. Data analysis in this study used univariate data analysis and bivariate data analysis by means of multiple linear regression, namely the development of simple linear regression.  Results: The results in this study were that there was a significant influence between the parenting style variable with a p-value of 0,0017 and t count of 2,487, breastfeeding status with a p-value of 0,006 and t of 2,926, and nutritional status with a p-value of 0,000 and t count 4,467 with the development of preschool children in PAUD Puspita.  Discussion: PAUD Puspita is expected to encourage and advise parents to maintain the nutritional status of children with a balanced diet.